Analytical crash analysis of heavy truck cabin structure according to regulation ECE-R29. Issue 1 (1st March 2022) - Ioniţă, A; Iozsa, M D; Stan, C; Manea, A M
Abstract: The safety of the occupants is the prime consideration for all commercial vehicles' structure design. The truck cabin must be designed in such a way that the deformation patterns of the cabin structure during an impact can assure sufficient survival space for occupants. The objective of this study is to develop a CAD method to see the behaviour of the cab structure under the impact loads and the dynamic responses of the cab structure during two complex tests in line with ECE-R29regulation. In this paper, a finite element model of a lightweight cabin is built by using its Computer-Aided Design (CAD) model (which was developed by using CATIA software) and subjected to tests by using Ansys software. The test was made in order to evaluate the energy management and the cab strength under the loads. Finally, a solution is suggested to improve the cab's response for optimization design in order to validate an ECE R29 test.